How are Human Rights in the Concept of a State? A Review Book 'Negara Hukum dan Asasi Manusia', Dr. Bahder Johan Nasution, S.H., SM., M.Hum., CV Mandar Maju, Bandung, 2017, 286 pages, ISBN: 978-979-538-382-6 - Pradana, Floribertus Bujana Adi (Faculty of Law, Universitas Negeri Semarang, 2021)
For a long time, the issue of the state of law and human rights has always been debated among state legal experts and political thinkers. The purpose is to find an ideal concept about the state of law and the protection of human rights. However, for centuries, the concept of the state of law and the protection of human rights that are considered ideal has always been a debate. Moreover, so far there has been an impression that understanding human rights protection is superficially understood because it is only seen as mere moral guidelines. That understanding is wrong understanding because the understanding is not only on the moral order but also on the legal order. The facts show that, as a result of a superficial understanding of human rights, respect and also the enforcement of human rights are often not carried out properly as envisioned by a state of law. Based on this fact, this book has been compiled by referring to various literatures on constitutional law, political science and philosophy, which also describe the concept of the state of law and human rights, the concept of sovereignty and democracy, and the concepts of protection and the enforcement of human rights. Thus, the reader's understanding of the concept of the state of law and human rights can be understood in its entirety The understanding is not only in the concept of the state of law in legal formal way, but also in understanding more theoretical and philosophical concepts. Likewise, the understanding of human rights is also not only about conceptual understanding, but also understanding in the form of respect and protection of human rights implemented through the enforcement of human rights law.